2022
DOI: 10.3389/fcvm.2022.991586
|View full text |Cite
|
Sign up to set email alerts
|

Selexipag-based triple combination therapy improves prognosis in Chinese pulmonary arterial hypertension patients

Abstract: AimSelexipag is an oral selective prostacyclin receptor agonist approved for treatment of patients with pulmonary arterial hypertension (PAH). In the present study, we aim to assess the safety and efficacy of selexipag in triple combination therapy with endothelial receptor antagonists (ERAs) and PDE5is for Chinese PAH patients.Methods and resultsA single center retrospective study was performed on group 1 PAH patients (n = 68) initiating triple combination therapy with selexipag from 1 February 2020 to 31 Aug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…These findings align with the 2022 ESC/ERS Guidelines for the diagnosis and treatment of pulmonary hypertension 9 . However, Cui et al reported a higher 1‐year event‐free survival rate of 96.7% in PAH patients who received selexipag‐based initial triple combination therapy 17 . The difference in our data may be due to variations in gender ratios, risk stratification, and the type of initial triple or sequential triple combination therapy.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…These findings align with the 2022 ESC/ERS Guidelines for the diagnosis and treatment of pulmonary hypertension 9 . However, Cui et al reported a higher 1‐year event‐free survival rate of 96.7% in PAH patients who received selexipag‐based initial triple combination therapy 17 . The difference in our data may be due to variations in gender ratios, risk stratification, and the type of initial triple or sequential triple combination therapy.…”
Section: Discussionsupporting
confidence: 87%
“… 9 However, Cui et al reported a higher 1‐year event‐free survival rate of 96.7% in PAH patients who received selexipag‐based initial triple combination therapy. 17 The difference in our data may be due to variations in gender ratios, risk stratification, and the type of initial triple or sequential triple combination therapy. Nevertheless, previous studies and our own indicated that selexipag‐based initial triple combination therapy has a positive impact on the prognosis of PAH patients.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“… 2 However, most such studies analyzed patients who were treated with oral drugs and parenteral administration of prostanoids, 5 , 6 , 7 while others had small sample sizes and were single‐center studies. 8 , 9 Therefore, evidence regarding the efficacy and safety of oral triple combination therapy remains scarce.…”
Section: Introductionmentioning
confidence: 99%